Nitrogen-zinc co-doped neodymium sulfide / foamy copper composite electrode material and preparation method and application thereof

By growing nitrogen and zinc co-doped neodymium sulfide in situ on the foam copper matrix, the conductivity and structural stability of the neodymium sulfide electrode material is solved, and a high-performance supercapacitor electrode material is achieved, with excellent energy storage performance and long cycle life.

CN120261176APending Publication Date: 2025-07-04HANDAN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510652918.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

As a supercapacitor electrode material, neodymium sulfide has problems such as low conductivity, poor structural stability, and prone to volume expansion and agglomeration during charging and discharging, which limits its application in supercapacitors.

Method used

Nitrogen-zinc co-doped neodymium sulfide/foam copper composite electrode material is used to coat nitrogen-zinc co-doped neodymium sulfide outside the foam copper matrix, and the doping of zinc increases the sulfur vacancies in the active material, promotes ion diffusion and redox reactions, nitrogen-doped increases the layer spacing and improves the active site, and foam copper provides three-dimensional network structure stability.

Benefits of technology

It significantly improves the energy storage performance and cycle stability of the material, provides high specific capacity and long cycle life, and is suitable for new energy, military industry and wearable equipment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120261176A_ABST
    Figure CN120261176A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials, and particularly discloses a nitrogen-zinc co-doped neodymium sulfide / foamy copper composite electrode material and a preparation method and application thereof. According to the invention, foamy copper is used as a substrate, and the nitrogen-zinc co-doped neodymium sulfide / foamy copper composite electrode material is directly obtained through in-situ growth by a one-step hydrothermal method. The composite electrode material provided by the invention has relatively high specific capacity and stability, the specific capacitance can reach 2820.8 F / g under the current density of 25A / g, the capacity retention rate after 20000 cycles is 349.5%, the energy storage performance and the cycle performance are excellent, an excellent composite electrode material is provided for preparing a high-performance supercapacitor, and the preparation method is wide in raw material source and low in cost. The preparation method has the advantages of low price, simple and feasible preparation process, high preparation efficiency and wide application prospect, and can be used for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and particularly to a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, a preparation method thereof, and an application thereof. Background Art

[0002] As a new type of energy storage device, supercapacitors have shown broad application prospects in the fields of new energy vehicles, smart grids, portable electronic devices, etc. due to their significant advantages such as high power density, fast charge and discharge capabilities, and ultra-long cycle life. However, the performance of electrode materials is the key factor determining the energy density and cycle stability of supercapacitors. Developing high-performance electrode materials has become the core research direction for improving the comprehensive performance of supercapacitors.

[0003] Currently, transition metal sulfides have been widely used in supercapacitor electrode materials due to their abundant redox active sites and high theoretical specific capacitance. Neodymium sulfide has a high theoretical specific capacitance (>800 F / g) and a wide potential window, and is regarded as an ideal candidate for the next generation of high-performance supercapacitor electrode materials. However, neodymium sulfide has problems such as low conductivity, poor structural stability, easy volume expansion and aggregation during charge and discharge processes, resulting in reduced utilization rate of active substances, and further limiting the energy density and cycle life of supercapacitors. A single neodymium sulfide material is difficult to meet the requirements of practical applications for high-performance electrode materials.

[0004] Therefore, there is an urgent need to develop a method that can effectively improve the electrochemical performance of neodymium sulfide, provide a new solution for improving the energy density, power density and cycle stability of supercapacitors, and meet the growing energy storage needs. Summary of the Invention

[0005] Aiming at the problems that the existing neodymium sulfide as an electrode material has low conductivity, poor structural stability, easy volume expansion and aggregation during charge and discharge processes, which seriously limit its application in supercapacitors, the present invention provides a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, a preparation method thereof, and an application thereof.

[0006] To solve the above technical problems, the technical solution provided by the present invention is:

[0007] A nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, comprising a copper foam matrix and nitrogen and zinc co-doped neodymium sulfide coated on the outside of the copper foam matrix.

[0008] Compared with the prior art, the composite electrode material provided by the present invention has zinc and nitrogen co-doped neodymium sulfide coated on the outside of copper foam. The doping of Zn can increase the concentration of sulfur vacancies in the neodymium sulfide active material, thereby promoting the change of the local electron concentration around the generated sulfur vacancies, which is beneficial to promoting the diffusion of ions, thus promoting the occurrence of the redox reaction rate, increasing the active sites of the reaction, and thereby improving the energy storage performance of the material; N doping can increase the layer spacing of the neodymium sulfide active material, further increase the concentration of sulfur vacancies in the active material, improve the diffusion rate of ions, increase the active sites of the reaction, and increase the energy storage of the material. The doping of Zn atoms can significantly improve the structural stability of the active material. At the same time, the presence of three-dimensional network copper foam can not only increase the loading amount of N-doped Nd2S3 active material, but also further slow down the volume expansion during charge and discharge, thus being beneficial to the further improvement of the energy storage performance of the electrode material and enhancing the cycle stability performance of the electrode material.

[0009] Through the co-doping of zinc ions and nitrogen atoms in the Nd2S3 electrode material and the good conductive network of copper foam, the present invention synergistically enables the composite electrode material to exhibit high electrochemical performance and has broad application prospects in the field of supercapacitors.

[0010] The present invention also provides a preparation method of a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, which includes the following steps:

[0011] S1, adding soluble neodymium salt, soluble zinc salt and thiourea into a mixed solution of ethylene glycol and water to obtain a precursor solution;

[0012] S2, placing the precursor solution and the copper foam substrate in a hydrothermal kettle, reacting at 130°C to 180°C, washing and drying to obtain a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material.

[0013] The present invention uses copper foam as the substrate. The three-dimensional porous structure of copper foam can provide a high specific surface area, which is beneficial to the loading of active substances and ion transport; at the same time, its high conductivity can improve the conductivity of the overall electrode and reduce the resistance; in addition, the mechanical strength of copper foam can also relieve the volume expansion of neodymium sulfide during charge and discharge and extend the cycle life. Zn atoms can be embedded between the layers of neodymium sulfide to expand the layer spacing, relieve the volume expansion stress, and stabilize the lattice structure through Zn-S bonding; the vacancy defects generated by N doping can be used as ion storage sites to increase the specific capacitance.

[0014] The present invention solves the problems of poor conductivity of the neodymium sulfide electrode, easy collapse of the structure, easy volume expansion and aggregation during charge and discharge through the in-situ synthesis method, providing a material basis for the large-scale application of supercapacitors in the fields of new energy, military, wearable devices, etc.

[0015] Specifically, before the hydrothermal reaction, the copper foam substrate needs to be pretreated to remove impurities on the surface of the copper foam.

[0016] Further, after cutting the copper foam into small pieces, the copper foam is ultrasonically treated in acetone for 15 min to 20 min, and then ultrasonically treated in hydrochloric acid solution and deionized water for 15 min to 20 min respectively to obtain a clean copper foam substrate.

[0017] As a specific embodiment of the present invention, the concentration of the above-mentioned hydrochloric acid solution is 2.5 M to 3.5 M. The copper foam can be cut into a size of 2 cm × 5 cm × 1.5 mm.

[0018] Further, the soluble neodymium salt is neodymium chloride, neodymium sulfate or neodymium nitrate.

[0019] Further, the soluble zinc salt is zinc chloride, zinc sulfate or zinc nitrate.

[0020] It should be noted that the soluble neodymium salt and the soluble zinc salt are salts with the same anion. For example, if the soluble neodymium salt is neodymium chloride, the soluble zinc salt is preferably zinc chloride.

[0021] Further, in the precursor solution, the concentration of the soluble neodymium salt is 5 mmol / L to 15 mmol / L, the concentration of the soluble zinc salt is 0.4 mmol / L to 1.8 mmol / L, and the concentration of thiourea is 15 mmol / L to 25 mmol / L.

[0022] Preferably, the volume ratio of ethylene glycol to water is 1:1.5 to 1:2.5.

[0023] Further, in S2, the reaction time is 4 h to 8 h.

[0024] Under the preferred above reaction conditions, the uniform growth of nitrogen and zinc co-doped neodymium sulfide on the surface of copper foam can be promoted, a complete and dense coating layer can be formed, and the electronic structure and crystal structure of the material can be optimized, thereby improving the conductivity and stability of the material and enhancing the overall performance of the composite electrode material.

[0025] The present invention also provides a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, which is prepared by the preparation method of the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material described in any one of the above.

[0026] The present invention directly obtains a nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material through a one-step hydrothermal method by in-situ growth. A tight and firm interfacial bond can be formed between neodymium sulfide and copper foam, avoiding problems such as film peeling and loose bonding that may occur in traditional coating or deposition methods. The firm interfacial bond not only facilitates the efficient transmission of electrons between the substrate and the active material but also enhances the overall stability and mechanical properties of the composite electrode material, enabling it to maintain good performance in subsequent electrochemical applications and extending the cycle stability.

[0027] The present invention also provides a positive electrode comprising the above-mentioned nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material.

[0028] The present invention also provides a supercapacitor comprising the above-mentioned positive electrode.

[0029] There is no binder between the zinc and nitrogen co-doped neodymium sulfide and copper foam in the present invention. The zinc ion and nitrogen atom co-doped Nd2S3 electrode material is in-situ prepared on the copper foam substrate under specific conditions. Through the unique core-shell microtopography structure and the improvement effect of Zn and N co-doping on the lattice of the Nd2S3 active material, the electron transport rate and ion transfer rate in the material are significantly improved, thereby significantly enhancing the energy storage performance.

[0030] The composite electrode material provided by the present invention has a high specific capacitance and stability. At a current density of 25 A / g, the specific capacitance can reach 2820.8 F / g, and the capacity retention rate after 20,000 cycles is 349.5%. It has excellent energy storage performance and cycle performance, providing a superior composite electrode material for the preparation of high-performance supercapacitors. Moreover, the raw materials of the preparation method are widely sourced, low in price, the preparation process is simple and easy to implement, the preparation efficiency is high, large-scale production can be carried out, and it has broad application prospects. Description of the Drawings

[0031] Figure 1 XRD pattern of the nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material prepared in Example 1 of the present invention;

[0032] Figure 2 SEM images of the nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material prepared in Example 1 of the present invention and the nitrogen-doped neodymium sulfide / copper foam composite electrode material prepared in Comparative Example 1 at different magnification levels; wherein, (a) to (d) are Comparative Example 1; (e) to (h) are Example 1;

[0033] Figure 3 SEMMapping energy spectrum diagram of the nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material prepared in Example 1 of the present invention;

[0034] Figure 4TEM images and TEM Mapping images of the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1 of the present invention; among them, (a)-(b) TEM images at different magnifications, (c) high-resolution transmission electron microscopy image, (d) electron diffraction pattern, (e) TEM Mapping image;

[0035] Figure 5 XPS images of the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1 of the present invention; among them, (a) full spectrum image, (b) S2p, (c) N 1s, (d) Nd 3d, (e) Zn2p, (f) C 1s;

[0036] Figure 6 Specific capacitance-current density diagrams of the composite electrode materials prepared in Examples 1-3 and Comparative Example 3;

[0037] Figure 7 Cyclic voltammograms of the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1 at different scanning rates;

[0038] Figure 8 Electrochemical impedance diagrams of the composite electrode materials prepared in Examples 1-3 and Comparative Example 3, where the upper right corner is a partial enlarged view of the circled part;

[0039] Figure 9 Retention rate diagrams of the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1;

[0040] Figure 10 Cyclic voltammograms of the aqueous supercapacitor assembled with the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1 as the positive electrode and the Pd@N-Cu7S4 / NF material as the negative electrode in 1M KOH electrolyte at different scanning rates;

[0041] Figure 11 Galvanostatic charge-discharge curves of the aqueous supercapacitor assembled with the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1 as the positive electrode and the Pd@N-Cu7S4 / NF material as the negative electrode in 1M KOH electrolyte at different mass current densities;

[0042] Figure 12 Electrochemical impedance diagram of the aqueous supercapacitor assembled with the nitrogen-zinc co-doped neodymium sulfide / carbon foam composite electrode material prepared in Example 1 as the positive electrode and the Pd@N-Cu7S4 / NF material as the negative electrode in 1M KOH electrolyte, where the upper right corner is a partial enlarged view of the circled part;

[0043] Figure 13Ragone plot of an aqueous supercapacitor assembled with the nitrogen and zinc co-doped neodymium sulfide / cupric foam composite electrode material prepared in Example 1 as the positive electrode and the Pd@N-Cu7S4 / NF material as the negative electrode in a 1 M KOH electrolyte. Detailed implementation manners

[0044] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] To better illustrate the present invention, further illustrative examples are given below through embodiments.

[0046] Example 1

[0047] A preparation method of a nitrogen and zinc co-doped neodymium sulfide / cupric foam composite electrode material:

[0048] Step 1: Cut commercial cupric foam into rectangular strips with a size of 2 cm × 5 cm × 1.5 mm, add them to acetone and ultrasonically treat for 20 min, then ultrasonically treat with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry to obtain a cupric foam substrate.

[0049] Step 2: Add neodymium chloride, zinc chloride and thiourea to a mixed solution of ethylene glycol and water with a volume ratio of 1:2 to obtain a precursor solution; the concentration of neodymium chloride in the precursor solution is 10 mmol / L, the concentration of zinc chloride is 1.0 mmol / L, and the concentration of thiourea is 20 mmol / L.

[0050] Step 3: Add the cupric foam substrate and the above precursor solution to a high-pressure hydrothermal autoclave, react at 140 °C for 4 h, after the reaction is completed, take out the cupric foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain a nitrogen and zinc co-doped neodymium sulfide / cupric foam composite electrode material, denoted as 1.0 Zn@N-Nd2S3 / FC.

[0051] Example 2

[0052] A preparation method of a nitrogen and zinc co-doped neodymium sulfide / cupric foam composite electrode material:

[0053] Step 1: Cut commercial cupric foam into rectangular strips with a size of 2 cm × 5 cm × 1.5 mm, add them to acetone and ultrasonically treat for 20 min, then ultrasonically treat with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry to obtain a cupric foam substrate.

[0054] Step 2: Add neodymium chloride, zinc chloride, and thiourea into a mixed solution of ethylene glycol and water with a volume ratio of 1:2.5 to obtain a precursor solution. The concentration of neodymium chloride in the precursor solution is 10 mmol / L, the concentration of zinc chloride is 0.5 mmol / L, and the concentration of thiourea is 20 mmol / L.

[0055] Step 3: Add the copper foam substrate and the above precursor solution into a high-pressure hydrothermal reactor, react at 130 °C for 8 h. After the reaction is completed, take out the copper foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, denoted as 0.5 Zn@N-Nd2S3 / FC.

[0056] Example 3

[0057] A preparation method of a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material:

[0058] Step 1: Cut commercial copper foam into rectangular strips of 2 cm × 5 cm × 1.5 mm, add them into acetone and ultrasonically treat for 20 min, then ultrasonically treat with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry to obtain a copper foam substrate.

[0059] Step 2: Add neodymium chloride, zinc chloride, and thiourea into a mixed solution of ethylene glycol and water with a volume ratio of 1:1.5 to obtain a precursor solution. The concentration of neodymium chloride in the precursor solution is 10 mmol / L, the concentration of zinc chloride is 1.5 mmol / L, and the concentration of thiourea is 20 mmol / L.

[0060] Step 3: Add the copper foam substrate and the above precursor solution into a high-pressure hydrothermal reactor, react at 180 °C for 4 h. After the reaction is completed, take out the copper foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, denoted as 1.5 Zn@N-Nd2S3 / FC.

[0061] Comparative Example 1

[0062] This comparative example provides a preparation method of a nitrogen-doped neodymium sulfide / copper foam composite electrode material:

[0063] Step 1: Cut commercial copper foam into rectangular strips of 2 cm × 5 cm × 1.5 mm, add them into acetone and ultrasonically treat for 20 min, then ultrasonically treat with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry to obtain a copper foam substrate.

[0064] Step 2: Add neodymium chloride and thiourea into a mixed solution of ethylene glycol and water with a volume ratio of 1:2 to obtain a precursor solution; the concentration of neodymium chloride in the precursor solution is 10 mmol / L, and the concentration of thiourea is 20 mmol / L.

[0065] Step 3: Add the copper foam substrate and the above precursor solution into a high-pressure hydrothermal reactor, react at 140 °C for 4 h. After the reaction is completed, take out the copper foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain a nitrogen-doped neodymium sulfide / copper foam composite electrode material, denoted as N-Nd2S3 / FC.

[0066] Comparative Example 2

[0067] This comparative example provides a preparation method of a nitrogen-manganese co-doped neodymium sulfide / copper foam composite electrode material:

[0068] Step 1: Cut commercial copper foam into rectangular strips with a size of 2 cm × 5 cm × 1.5 mm, add it into acetone and ultrasonically treat for 20 min, then ultrasonically treat with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry to obtain a copper foam substrate.

[0069] Step 2: Add neodymium chloride, manganese chloride and thiourea into a mixed solution of ethylene glycol and water with a volume ratio of 1:2 to obtain a precursor solution; the concentration of neodymium chloride in the precursor solution is 10 mmol / L, the concentration of manganese chloride is 1.0 mmol / L, and the concentration of thiourea is 20 mmol / L.

[0070] Step 3: Add the copper foam substrate and the above precursor solution into a high-pressure hydrothermal reactor, react at 140 °C for 4 h. After the reaction is completed, take out the copper foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain a nitrogen-manganese co-doped neodymium sulfide / copper foam composite electrode material, denoted as 1.0 Mn@N-Nd2S3 / FC.

[0071] Comparative Example 3

[0072] This comparative example provides a preparation method of a nitrogen-nickel co-doped neodymium sulfide / copper foam composite electrode material:

[0073] Step 1: Cut commercial copper foam into rectangular strips with a size of 2 cm × 5 cm × 1.5 mm, add it into acetone and ultrasonically treat for 20 min, then ultrasonically treat with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry to obtain a copper foam substrate.

[0074] Step 2: Add neodymium chloride, nickel chloride and thiourea into a mixed solution of ethylene glycol and water with a volume ratio of 1:2 to obtain a precursor solution; the concentration of neodymium chloride in the precursor solution is 10 mmol / L, the concentration of nickel chloride is 1.0 mmol / L, and the concentration of thiourea is 20 mmol / L.

[0075] Step 3: Add the copper foam substrate and the above precursor solution into a high-pressure hydrothermal reactor, react at 140 °C for 4 h. After the reaction is completed, take out the copper foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain the nitrogen and nickel co-doped neodymium sulfide / copper foam composite electrode material, denoted as 1.0 Ni@N-Nd2S3 / FC.

[0076] Comparative Example 4

[0077] This comparative example provides a method for preparing a nitrogen and cobalt co-doped neodymium sulfide / copper foam composite electrode material:

[0078] Step 1: Cut the commercial copper foam into rectangular strips of 2 cm × 5 cm × 1.5 mm, add it to acetone and ultrasonically treat it for 20 min, then ultrasonically treat it with 3 mol / L hydrochloric acid solution and deionized water for 15 min respectively, and dry it to obtain the copper foam substrate;

[0079] Step 2: Add neodymium chloride, cobalt chloride and thiourea into a mixed solution of ethylene glycol and water with a volume ratio of 1:2 to obtain a precursor solution; the concentration of neodymium chloride in the precursor solution is 10 mmol / L, the concentration of cobalt chloride is 1.0 mmol / L, and the concentration of thiourea is 20 mmol / L;

[0080] Step 3: Add the copper foam substrate and the above precursor solution into a high-pressure hydrothermal reactor, react at 140 °C for 4 h. After the reaction is completed, take out the copper foam, wash it thoroughly with pure water, and dry it in an oven at 60 °C to obtain the nitrogen and cobalt co-doped neodymium sulfide / copper foam composite electrode material, denoted as 1.0 Co@N-Nd2S3 / FC.

[0081] Material Characterization

[0082] Figure 1 Prepared for Example 1 1.0XRD pattern of Zn@N-Nd2S3 / FC. As can be seen from the figure, the diffraction peaks at 43.3°, 50.4° and 74.1° belong to the (1 1 1), (2 0 0) and (2 2 0) crystal planes of Cu (PDF#04-0836), respectively. The diffraction peaks at 24.6°, 25.9°, 28.0°, 32.7°, 33.3°, 34.7°, 36.5°, 38.5°, 40.4°, 44.9°, 46.4°, 48.4°, 52.6°, 56.1°, 61.9°, 66.9°, 69.6°, 71.5°, 73.1° and 76.2° belong to the (2 1 0), (1 4 0), (0 3 1), (2 0 1), (2 4 0), (2 2 1), (0 5 1), (1 5 1), (2 4 1), (0 02), (3 3 1), (1 7 1), (1 4 2), (3 6 1), (3 3 21), (0 8 2), (2 10 1), (1 1 3), (0 12 0) and (2 2 3) crystal planes of Nd2S3 (PDF#45-0984), respectively. It is proved that the prepared electrode material is the Zn@N-Nd2S3 / FC composite electrode material.

[0083] Figure 2 Prepared for Example 1 1.0 SEM images of Zn@N-Nd2S3 / FC prepared in Example 1 and N-Nd2S3 / FC prepared in Comparative Example 1 at different magnifications. Among them, (a)-(d) are the SEM images of N-Nd2S3 / FC prepared in Comparative Example 1, and (e)-(h) are those of 1.0 Zn@N-Nd2S3 / FC prepared in Example 1. By comparing the images (a)-(d) and (e)-(h), it can be seen that there are differences in the microtopographies of the nitrogen-doped neodymium sulfide / copper foam electrode material prepared in Comparative Example 1 and the nitrogen-zinc co-doped neodymium sulfide / copper foam electrode material prepared in Example 1.

[0084] Figure 3 Prepared for Example 1 1.0 SEM Mapping image of Zn@N-Nd2S3 / FC, which proves that the composite electrode material prepared in Example 1 is composed of Zn, Nd, S, N and Cu.

[0085] Figure 4 Prepared for Example 1 1.0 TEM image of Zn@N-Nd2S3 / FC. (a) and (b) are 1.0TEM images of the microstructure of Zn@N-Nd2S3 material (ultrasonically detached from copper foam for testing); the interplanar spacing in Figure (c) is 0.32 nm, belonging to the (03 1) crystal plane of Nd2S3. Figure (d) is the electron diffraction pattern, from which it can be clearly seen that the synthesized 1.0 Zn@N-Nd2S3 material has a single-crystal structure, indicating good crystallization performance. Figure (e) is 1.0 the TEM Mapping image of Zn@N-Nd2S3 material, from which it can be seen that 1.0 the Zn@N-Nd2S3 material is composed of four elements: nitrogen, sulfur, zinc, and neodymium.

[0086] Figure 5 Prepared for Example 1 1.0 XPS (X-ray photoelectron spectroscopy) image of Zn@N-Nd2S3 / FC. In Figure (a), the peaks at 163.0 eV, 285.0 eV, 399.0 eV, 532.0 eV, 932.0 eV, 1006.0 eV, and 1042.0 eV are the peaks of S, C, N, O, Cu, Nd, and Zn respectively. Figure (b) is the XPS spectrum of S2p, and the spectral peaks at 161.9 eV and 169.0 eV belong to S2p 1 / 2 and S2p 3 / 2 . Figure (c) is the XPS spectrum of N1s, and the spectral peak at 398.6 eV proves the doping of nitrogen atoms. The spectral peak at 406.0 eV belongs to the nitrogen in neodymium nitride. This result further proves the existence of nitrogen doping in the prepared 1.0 Zn@N-Nd2S3 / FC material. Figure (d) belongs to the XPS spectrum of Nd 3d, and the spectral peaks at 981.7 eV and 1004.2 eV belong to Nd 3d 3 / 2 and Nd 3d 5 / 2 . Figure (e) belongs to the XPS peak of Zn 2p, and the spectral peaks at 1019.5 eV and 1042.5 eV belong to Zn 2p 1 / 2 and Zn 2p 3 / 2 . Figure (f) is the XPS spectrum of C1s, and the spectral peak is 284.8 eV. Measuring the carbon element is for calibrating the peaks of other elements.

[0087] Performance Test

[0088] 1. Constant current charge-discharge test

[0089] The composite electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for galvanostatic charge-discharge curves (GCD) at different mass current densities (25 - 30 A / g) in a 1 M KOH electrolyte within the potential range of 0 - 0.6 V using a three-electrode system (the electrode to be tested as the positive electrode, the saturated calomel electrode as the reference electrode, and the platinum sheet as the negative electrode), and a specific capacitance-current density graph was plotted, as shown in Figure 6 shown. The specific capacitance C at different mass current densities was calculated based on the galvanostatic charge-discharge curves, and the results are shown in Table 1. The calculation formula is as follows:

[0090] C = i m t / ΔV

[0091] where C represents the specific capacitance, with the unit of F·g -1 ; i m represents the current density, with the unit of A·g -1 ; t represents the discharge time, with the unit of s; ΔV represents the potential difference, with the unit of V.

[0092] Table 1 Specific capacitance (F / g) at different mass current densities

[0093] Mass current density (A / g) 25 26 27 28 29 30 Example 1 2820.8 2803.7 2794.5 2781.3 2730.8 2695.0 Example 2 2800.0 2725.7 2722.5 2650.7 2624.5 2570.0 Example 3 2387.5 2374.7 2340.0 2324.0 2295.8 2260.0 Comparative Example 1 2087.5 2054.0 2016.0 2022.0 1917.7 1935 Comparative Example 2 1354.2 1342.0 1322.6 1314.1 1288.6 1274.5 Comparative Example 3 1441.7 1438.2 1426.5 1414.0 1404.6 1397.0 Comparative Example 4 1541.7 1534 1521 1512 1498.8 1481.5

[0094] As can be seen from the above table, the 1.0 Zn@N-Nd2S3 / FC composite electrode material prepared in Example 1 of the present invention has a high specific capacity at different mass current densities, which is higher than those of Examples 2 - 3 and Comparative Examples 1 - 4. 1.0 The specific capacitance values of the Zn@N-Nd2S3 / FC composite electrode material at current densities of 25 A / g, 26 A / g, 27 A / g, 28 A / g, 29 A / g, and 30 A / g are 2820.8 F / g, 2803.7 F / g, 2794.5 F / g, 2781.3 F / g, 2730.8 F / g, and 2695.0 F / g, respectively.

[0095] 1.0 The improvement in the performance of the Zn@N-Nd2S3 / FC composite electrode material is closely related to both the doping of zinc ions in the electrode material and the amount of zinc ion doping. The doping of zinc ions can promote the generation of sulfur vacancies inside the material. The generation of sulfur vacancies is beneficial to reducing the ion diffusion path, promoting ion transport and charge transfer, thereby enhancing the energy storage capacity of the electrode material. Therefore, the capacitance performance of the Zn@N-Nd2S3 / FC composite electrode material after zinc ion doping in Example 1 is higher than that in Comparative Example 1, and the capacitance performance of the zinc ion doping concentration in Example 1 is higher than that of the zinc ion doping concentrations in Examples 2 and 3. In addition, 1.0The performance of the Zn@N-Nd2S3 / FC composite electrode material is also related to the types of ions doped in the material. Therefore, the capacitance performance of zinc ion doping in Example 1 is significantly higher than that of manganese, nickel, and cobalt ion doping at the same ion doping concentration in Comparative Examples 2-4.

[0096] 2. Cyclic voltammetry curve

[0097] The 1.0 Zn@N-Nd2S3 / FC composite electrode material prepared in Example 1 was tested for cyclic voltammetry curves at different scanning rates (5 mV / s, 20 mV / s, 50 mV / s, 100 mV / s, 200 mV / s, 500 mV / s). In the potential range of 0-0.6 V, using a three-electrode system (the working electrode is the positive electrode, the saturated calomel electrode is the reference electrode, and the platinum sheet is the negative electrode), the cyclic voltammetry curve was tested in 1 M KOH electrolyte, and the results are as Figure 7 shown. It can be seen from the figure that at low scanning rates, 1.0 the cyclic voltammetry curve of the Zn@N-Nd2S3 / FC electrode material is similar to a rectangle, indicating good capacitance performance.

[0098] 3. Impedance test

[0099] The composite electrode materials prepared in Examples 1-3 and Comparative Example 1 were tested for electrochemical impedance in the voltage range of 0-0.6 V, the potential range of 10 mHz-0.1 MHz, and a perturbation voltage of 5 mV, using a three-electrode system (the working electrode is the positive electrode, the saturated calomel electrode is the reference electrode, and the platinum sheet is the negative electrode) in 1 M KOH electrolyte, and the results are as Figure 8 shown.

[0100] It can be seen from the figure that the N-Nd2S3 / FC composite electrode material prepared in Comparative Example 1 has a certain arc in the high-frequency region, while the 1.0 Zn@N-Nd2S3 / FC, 0.5 Zn@N-Nd2S3 / FC and 1.5 Zn@N-Nd2S3 / FC composite electrode materials have no semi-circle or obvious arc in the high-frequency region, indicating that the charge transfer resistance of the three materials in Examples 1-3 is relatively low. It can also be seen from the figure that the total resistance of the four electrode materials prepared in Examples 1-3 and Comparative Example 1 from large to small is: Example 3 > Comparative Example 1 > Example 1 > Example 2.

[0101] 4. Cycling stability

[0102] The composite electrode materials prepared in Examples 1 to 3 and Comparative Example 1 were tested for cyclic retention rate in a 1 M KOH electrolyte using a three-electrode system (the electrode to be tested as the positive electrode, the saturated calomel electrode as the reference electrode, and the platinum sheet as the negative electrode) at a current density of 50 A / g in the potential range of 0 to 0.6 V. The results are as Figure 9 shown.

[0103] As can be seen from the figure, after 20,000 cycles, the capacity retention rates of the nitrogen-doped 1.0 Zn@N-Nd2S3 / FC prepared in Example 1, the nitrogen-doped 0.5 Zn@N-Nd2S3 / FC prepared in Example 2, the nitrogen-doped 1.5 Zn@N-Nd2S3 / FC prepared in Example 3, and the N-Nd2S3 / FC prepared in Comparative Example 1 were 349.5%, 39.9%, 453.9%, and 118.0% respectively. After 20,000 cycles, the nitrogen-doped 1.5 Zn@N-Nd2S3 / FC prepared in Example 3 had the highest capacity retention rate, followed by Example 1, and Example 2 had the lowest capacity retention rate.

[0104] 5. Supercapacitor performance test

[0105] Using the 1.0 Zn@N-Nd2S3 / FC composite electrode material prepared in Example 1 as the positive electrode, the Pd@N-Cu7S4 / NF material (for the preparation method, see F. Tian et al Journal of Energy Storage 112(2025)115548) as the negative electrode, and 1 M KOH solution as the electrolyte, an aqueous supercapacitor was assembled. The cyclic voltammetry curves of this supercapacitor at 0 to 1.8 V and test scan rates of 5 mV·s -1 , 10 mV·s -1 , 20 mV·s -1 , 50 mV·s -1 are as Figure 10 shown. In the CV curve, it was observed that the shape of the curve was similar to a rectangle, indicating that the device had excellent capacitive performance.

[0106] The constant current charge-discharge curves (GCD) of this aqueous supercapacitor were tested at different mass current densities (2 to 10 A / g) in a 1 M KOH electrolyte in the potential range of 0 to 1.8 V. The results are as Figure 11 shown. At current densities of 2 A / g, 3 A / g, 4 A / g, 5 A / g, 6 A / g, and 10 A / g, the specific capacitance values of the device were 119.4 F / g, 99.7 F / g, 90 F / g, 78.0 F / g, 67.9 F / g, and 32.2 F / g respectively.

[0107] The electrochemical impedance of this aqueous supercapacitor was tested in 1 M KOH solution. The perturbation voltage used for the test was 5 mV, and the test results are as Figure 12 shown. By fitting the total resistance of the electrolyte, charge transfer resistance, and Warburg (W R 、W T and W P ) resistances with Z-view software, the values were 4.0 Ω, 2.7 Ω, 27.9 Ω, 1.0 Ω, and 0.4 Ω respectively. The small charge transfer resistance indicates that ions can achieve rapid charge transfer during the electrochemical reaction, proving that this supercapacitor device has good reaction kinetics.

[0108] Figure 13 is the Ragone plot of the above aqueous supercapacitor in 1 M KOH electrolyte. From the figure, the energy density of this device at a power density of 1800 W / kg can be calculated to be 53.7 Wh / kg.

[0109] The energy density calculation formula is as follows:

[0110]

[0111] where E represents the energy density, with the unit of Ws / kg; C represents the specific capacitance, with the unit of F / kg; and ΔV represents the potential difference, with the unit of V.

[0112] The high power density calculation formula is as follows:

[0113]

[0114] where P represents the power density, with the unit of W / kg; E represents the energy density, with the unit of Ws / kg; and Δt represents the time, with the unit of s.

[0115] In summary, the present invention uses a one-step hydrothermal method to in-situ prepare 1.0 Zn@N-Nd2S3 / FC electrode material on a copper foam substrate. Due to the doping of zinc ions in the nitrogen-doped Nd2S3 electrode material and the good conductive network of copper foam, the composite electrode material exhibits high electrochemical performance. The specific capacitance of the aqueous symmetric supercapacitor prepared with it as the positive electrode material is 119.4 F / g (214.9 C / g) at a current density of 2.0 A / g, and the energy density is 53.7 Wh / kg at a power density of 1800 W / kg. This method provides a basis for optimizing the electrochemical performance of supercapacitor energy storage devices and improving their overall effects.

[0116] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material, characterized in that, It includes a copper foam matrix and neodymium sulfide doped with nitrogen and zinc coated on the outside of the copper foam matrix.

2. The preparation method of the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 1, characterized in that, It includes the following steps: S1. Add soluble neodymium salt, soluble zinc salt and thiourea into a mixed solution of ethylene glycol and water to obtain a precursor solution. S2. Place the precursor solution and the copper foam matrix in a hydrothermal autoclave, react at 130°C to 180°C, wash and dry to obtain a nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material.

3. The preparation method of the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 2, wherein, The soluble neodymium salt is neodymium chloride, neodymium sulfate or neodymium nitrate; and / or The soluble zinc salt is zinc chloride, zinc sulfate or zinc nitrate.

4. The preparation method of the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 2 or 3, characterized in that, In the precursor solution, the concentration of the soluble neodymium salt is 5 mmol / L to 15 mmol / L, the concentration of the soluble zinc salt is 0.4 mmol / L to 1.8 mmol / L, and the concentration of thiourea is 15 mmol / L to 25 mmol / L.

5. The preparation method of the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 2, characterized in that, The volume ratio of ethylene glycol to water is 1:1.5 to 1:2.

5.

6. The preparation method of the nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 2, characterized in that, In S2, the reaction time is 4 h to 8 h.

7. The preparation method of the nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 2, characterized in that, Before use, the copper foam is subjected to the following pretreatment process: Ultrasonically treat the copper foam in acetone for 15 min to 20 min, and then ultrasonically treat it in hydrochloric acid solution and deionized water for 15 min to 20 min respectively.

8. A nitrogen-zinc co-doped neodymium sulfide / copper foam composite electrode material, characterized in that, It is prepared by the preparation method of the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material according to any one of claims 2 to 7.

9. A positive electrode, characterized in that, It includes the nitrogen and zinc co-doped neodymium sulfide / copper foam composite electrode material according to claim 8.

10. A supercapacitor, characterized in that, It includes the positive electrode according to claim 9.